Investigation and Analytical Applications of the Reaction of N1-methylnicotinamide and Active Methylene Containing Drugs - Elsebaie, Heba A.; Elhamamsy, Mervat H.; Elokely, Khaled M.; Eldawy, Mohammed A. (Current Pharmaceutical Analysis, 2021)
Background: The reaction between N1-methylnicotinamide iodide (NMNI) and the active methylene group-containing compounds yields a fluorescent product, which can be used in the quantitative determination of certain drugs. Objective: The objective is to develop, adapt, and validate a simple spectrofluorometric method for the quantitative analysis of modafinil 1, budesonide 2, allicin 3, and florfenicol 4. Methods: Spectral analysis (elemental analysis, 1H, 13C NMR, MS), computational methods (geometry optimization, Gibbs free energy and pKa calculations) and spectrofluorometric approaches were conducted. Result: A C4 cyclization pathway was confirmed for the formation of the fluorophore. The spectrofluorometric method showed good linearity (R2= 0.996-0.999) over concentrations of 1-50 ng/mL, 0.5-5 ng/mL, 60-150 pg/mL, and 1-15 ng/mL of the standard solutions of 1, 2, 3, and 4, respectively. Conclusion: The proposed method is simple and suitable for quality control and assurance studies.
Keywords: budesonide